Drivers of Regional Destination Competitiveness: A DEMATEL – Fuzzy TOPSIS Approach - Rio Benedicto Bire; Agustino Lukas Fischer Conterius; Asbi Nasar (Faculty of Geography, Universitas Gadjah Mada, 2021)
This paper aims to explore a conceptual criteria framework for measuring tourism destination competitiveness at the regional level to fill the existing gap in literature. This study was conducted in the East Nusa Tenggara (NTT) Province of Indonesia, by developing a tailored set of criteria for measuring destination competitiveness specific for the regional backdrop through rigorous literature review and in-depth interviews with tourism experts. Moreover, a hybrid MCDM approach combining DEMATEL and Fuzzy TOPSIS techniques was employed to analyze interrelationships and importance rankings of the developed measurement criteria. This research developed a six-factor and twenty-three indicator framework deemed relevant for assessing destination competitiveness at the regional level. The six factors comprise of destination attraction, general infrastructure, superstructure, destination management, price competitiveness, and regional government policy. The DEMATEL analysis revealed regional government policy to be the most influential factor, whilst destination attraction was rendered the most important one. Results from the Fuzzy TOPSIS present the most important indicators from the framework as a natural attraction, accessibility and port infrastructure, accommodation, the image of the destination, and priority towards the tourism sector. Findings from this research provide valuable insights in terms of proposing tourism policymakers with a blueprint of regional destination competitiveness criteria that offers critical inputs for developing medium and long-term tourism strategies.